TiO(2) Nanomembranes Fabricated by Atomic Layer Deposition for Supercapacitor Electrode with Enhanced Capacitance - Naeem, Farah (Nanoscale Res Lett, 2019)
TiO(2) is a promising environment friendly, low cost, and high electrochemical performance material. However, impediments like high internal ion resistance and low electrical conductivity restrict its applications as electrode for supercapacitor. In the present work, atomic layer deposition was used to fabricate TiO(2) nanomembranes (NMs) with accurately controlled thicknesses. The TiO(2) NMs were then used as electrodes for high-performance pseudocapacitors. Experimental results demonstrated that the TiO(2) NM with 100 ALD cycles had the highest capacitance of 2332 F/g at 1 A/g with energy density of 81 Wh/kg. The enhanced performance was ascribed to the large surface area and the interconnectivity in the case of ultra-thin and flexible NMs. Increased ALD cycles led to stiffer NMs and decreased capacitance. Moreover, one series of two supercapacitors can light up one light-emitting diode with a working voltage of ~ 1.5 V, sufficiently describing its application values. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s11671-019-2912-3) contains supplementary material, which is available to authorized users.